A Network Flow Model for Irrigation Water Management - Murthy, A.; Murthy, G. (Algorithmic Operations Research, 2012)
Irrigation water management plays a crucial role in the growth and prosperity of countries like India. Optimization Techniques can be effectively used in the management of irrigation water. Motivated by a real crisis in Andhra Pradesh, India, the authors made an attempt to provide scientific solution to the problem of management of Pennar Delta System of Nellore District in Andhra Pradesh. The problem concerns the management of water distribution and scheduling for given requirements and availabilities of water at various nodes of the irrigation network of the system. This article provides a model and framework for the problem in question. The problem is formulated as a dynamic minimum cost network flow problem and provides an approach to solve the problem using static network flow models. A need based software is also developed to solve the network flow problems. Some issues in the programming are discussed.